Synthesis of Materials Based on La2O3 and SiO2 as Growth Stimulants for Salvia miltiorrhiza Bunge - Mai, Nguyen Vu Ngoc; Na, Nguyen Thi Ly; Phuong, Tran Thi Thu; The, Do Minh; Binh, Nguyen Thi Thanh; Tien, Vo Manh; Quoc, Nguyen Tri; Chi, Nguyen Thi Phuong Le; Tung, Mai Hung Thanh; Hoang, Cao Van (VNU Journal of Science: Natural Sciences and Technology; Vol 40 No 1DO - 10.25073/2588-1140/vnunst.5604, 2024)
In this paper, La 2 O 3 /SiO 2 material was synthesized and applied for growth stimulants of Salvia miltiorrhiza Bunge. La 2 O 3 /SiO 2 material was successfully synthesized from La(NO 3 ) 3 and SiO 2 precursors by solid-phase thermal method. The material properties were confirmed through physicochemical characterization methods including XRD, EDX, IR, and SEM analysis. The results of using La 2 O 3 /SiO 2 as a stimulating plant growth material for Salvia miltiorrhiza plants indicated that the use of La 2 O 3 /SiO 2 on Salvia miltiorrhiza plants had a significant effect. In the experimental model, the dry root yield increased by 0.27 tons/hecta, the root length increased by 3.6 cm on average, and the harvest time for Salvia miltiorrhiza was eleven days earlier. Additionally, the Salvia miltiorrhiza with La 2 O 3 /SiO 2 material was tougher than that without it, and gold leaf symptom was not observed in the experimental Salvia miltiorrhiza . Thus, the data suggested that La 2 O 3 /SiO 2 had a favorable effect on alvia miltiorrhiza the harvest time for Salvia miltiorrhiza was eleven days.